2018
DOI: 10.3390/cancers10090321
|View full text |Cite
|
Sign up to set email alerts
|

miR-9-5p in Nephrectomy Specimens is a Potential Predictor of Primary Resistance to First-Line Treatment with Tyrosine Kinase Inhibitors in Patients with Metastatic Renal Cell Carcinoma

Abstract: Approximately 20–30% of patients with metastatic renal cell carcinoma (mRCC) in first-line treatment with tyrosine kinase inhibitors (TKIs) do not respond due to primary resistance to this drug. At present, suitable robust biomarkers for prediction of a response are not available. Therefore, the aim of this study was to evaluate a panel of microRNAs (miRNAs) in nephrectomy specimens for use as predictive biomarkers for TKI resistance. Archived formalin-fixed, paraffin embedded nephrectomy samples from 60 mRCC … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 67 publications
(127 reference statements)
0
19
0
Order By: Relevance
“…Thus, all these expression particularities and further the characteristics of uncorrelated differential expression in relation to conventional clinicopathological factors are specific for orthogonal biomarkers [47]. Consequently, new information can arise from the application of such biomarkers in clinical practice [48]. Indeed, multivariate Cox regression analysis showed that the RNA signatures developed with circEGLN3, circRHOBTB3, and linRHOBTB3 proved their hypothesized prognostic value for all three clinical endpoints (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, all these expression particularities and further the characteristics of uncorrelated differential expression in relation to conventional clinicopathological factors are specific for orthogonal biomarkers [47]. Consequently, new information can arise from the application of such biomarkers in clinical practice [48]. Indeed, multivariate Cox regression analysis showed that the RNA signatures developed with circEGLN3, circRHOBTB3, and linRHOBTB3 proved their hypothesized prognostic value for all three clinical endpoints (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Successful independent validation of potentially predictive miRNAs remains a challenge. Overlap of results is rare in published studies of miRNAs as predictors of response to sunitinib in mRCC (8,(28)(29)(30). This could be partly due to tumor heterogeneity, various technologies used for miRNA analysis, limited numbers of enrolled patients, and failure to include a validation cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, this expression of RNAs mostly independent from clinicopathological variables and the other mentioned particular correlations is a key characteristic of orthogonal biomarkers [ 96 ]. Biomarkers of this kind are a real prerequisite for gaining information additional to that derived from established variables and for improving, for example, the prediction accuracy of a clinical outcome endpoint [ 97 ].…”
Section: Discussionmentioning
confidence: 99%